æ±‰è¯ä¸Žå°å°¼è¯æˆè¯ä¸çš„äº”ç§æ¤ç‰©æ–‡åŒ–æ„ä¹‰å¯¹æ¯”åˆ†æž - Afrina, Uray; Thamrin, Lily; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Idioms are the essential part ofÂ  Mandarin and Indonesian. Plant idiom have a lively and profound meaning because it is based on plant imagery.This paper used "Dictionary of Idioms" and "Kamus Peribahasa" to compile and analyze five plant elements meaning of plant idiom. Through comparative analysis, the author summarizes that in Mandarin and Indonesian plant idioms most of the "tree, wood, flower, grass, bamboo " can represent or describe human being or describe characters, things, things. Â The author is wishing can help Mandarin teachers and Mandarin learners on their learning process. Students can learn Chinese idioms better, improve their comprehension and their use idiom ability. Help Mandarin teachers to find the right one of teaching idiom pedagogy. Keywords: Mandarin, Indonesian, plants idiom, comparative analysisæ‘˜è¦ï¼šæ¤ç‰©æˆè¯æ˜¯å€Ÿç”¨ æ¤ç‰©æ„è±¡è¡¨è¾¾æˆè¯çš„æ„ä¹‰ï¼Œå› æ¤æ¤ç‰©æˆè¯çš„æ¤ç‰©è¯ç´ æ„ä¹‰ä½“çŽ°æ—¢ç”ŸåŠ¨åˆæ·±åˆ»ã€‚Â  æœ¬æ–‡ä»Žã€Šæˆè¯å¤§è¯å…¸ã€‹ä¸Žã€ŠKamus Peribahasaã€‹ä¸¤æœ¬è¯å…¸ä¸æ”¶é›†ä¸Žåˆ†æžäº†æ¤ç‰©æˆè¯çš„äº”ç§æ¤ç‰©è¯ç´ çš„æ–‡åŒ– æ„ä¹‰ã€‚é€šè¿‡å¯¹æ¯”åˆ†æžæ³•ï¼Œåˆ†æžåˆ°äº†ä¸€ä¸‹ç»“æžœï¼šä»Žæ„ä¹‰æ–¹é¢ä¸Šæ¥çœ‹ï¼Œæ±‰è¯æ¤ç‰©æˆè¯ä¸Žå°å°¼è¯æ¤ç‰©æˆè¯ä¸çš„â€œæ ‘ã€æœ¨ã€ èŠ±ã€è‰ã€ç«¹â€è¯ç´ å¤§éƒ¨åˆ†æ˜¯åŒæ ·å¯ä»¥è¡¨ç¤ºäººæˆ–å½¢å®¹äººç‰©ã€äº‹ç‰©ã€äº‹æƒ…ã€‚åˆ†æžä¹‹åŽï¼Œç¬”è€…å¸Œæœ›å¯¹æ±‰è¯æ•™å¸ˆä¸Žæ±‰è¯å¦ä¹ è€…æœ‰æ‰€å¸®åŠ©ã€‚å¯¹å¦ç”Ÿæ›´å¥½åœ° å¦ä¹ æ±‰è¯æˆè¯ï¼Œæ é«˜æˆè¯çš„ç†è§£èƒ½åŠ›å’Œè¿ç”¨èƒ½åŠ›ã€‚å¯¹æ•™å¸ˆåŠ©äºŽæ‰¾åˆ°åˆé€‚çš„æ•™æˆè¯çš„æ•™å¦æ³•ã€‚ å…³é”®è¯ï¼šæ±‰è¯ å°å°¼è¯ æ¤ç‰©æˆè¯ å¯¹æ¯”åˆ†æž